EGFR exon 20 insertion in lung adenocarcinomas among Hispanics (geno1.2-CLICaP). (November 2018) - Cardona, Andrés F.; Rojas, Leonardo; Zatarain-Barrón, Zyanya Lucia; Freitas, Helano C.; Granados, Sara T.; Castillo, Omar; Oblitas, George; Corrales, Luis; Castro, Christian D.; Ruiz-Patiño, Alejandro; Martín, Claudio; Pérez, María Angelina; et al.
Highlights: Among 4005 lung adenocarcinoma patients we identified 88 EGFR exon 20 insertions. Most patients with an exon 20 insertion were female and never-smokers. 36.4% of the patients had a concomitant EGFR-TKI sensitizing mutation. 81.7% of the patients had positive PD-L1 expression (>1%). OS was 16.4 months, and was influenced by a concomitant TKI-sensitizing mutation. Abstract: Objectives: Contrasting other EGFR mutations ( EGFR m) in lung adenocarcinomas, insertions in exon 20 (exon20ins) are generally associated with resistance to targeted therapy, limiting therapeutic options and impoverishing the prognosis compared to other EGFR m. We sought to extensively characterize exon20ins from a large cohort of lung adenocarcinomas in Hispanic patients. Materials and methods: This was a region-wide, observational longitudinal cohort study to evaluate characteristics and outcomes of patients with exon20ins in lung adenocarcinoma, based on a secondary analysis of electronic records from the Geno1.2-CLICaP Platform and extended genotype testing. Patients from six Latin-American countries were included (Argentina, Colombia, Costa Rica, Ecuador, Panama, and Mexico). Data obtained included the molecular spectrum (extended genotyping for mutations in BRAF, NRAS, PIK3CA, Her2 and MEK1, as well as for EGFR amplification, ALK and PD-L1 protein expression), clinic-pathologic characteristics, prevalence and outcomes to therapeutic approach. Results and conclusions: 4.005 patients diagnosed with stage III/IV lung adenocarcinoma from 2011 to 2016 were initially screened. Among these, 88 patients had a confirmed exon20 in. and were included; median age was 66-years, 62.5% were females, 64% were never smokers and 39% presented with brain metastases. The H773insH variant was the most frequent, making up 21.6% of cases. A common EGFR m was concomitantly found in 36.4% (del19/L858R), and 8% (G719X/L861Q/S768I) of cases. Five cases had additional mutations in PI3K, KRAS and MEK1, 26% had EGFR amplification and 81.7% had PD-L1 expression 1–50%. Overall response rate to first-line therapy was 28% and overall survival was 16.4 months. Prognosis was positively influenced by the concomitant presence of common EGFR m and response to first-line. Our results suggest that patients with EGFR exon20ins have similar clinical characteristics to those with common EGFR m but a poorer prognosis. Last, the mean PD-L1 expression in this population seems higher than for patients with common EGFR m.